PENETAPAN KADAR FENOLIK TOTAL TUMBUHAN ENDEMIK KALIMANTAN UTARA - Nasywa Amelsya Salsabillah; Aktsar Roskiana Ahmad; Rezki Amriati Syarif (Universitas Malahayati, 2025)
North Kalimantan is home to a unique biodiversity, including medicinal plants traditionally used by local communities such as the Dayak people. Several of these plants are endemic—found exclusively in this region. Two notable endemic species, Dayak onion (Eleutherine palmifolia (L.) Merr.) and rose myrtle (Rhodomyrtus tomentosa), are known to contain secondary metabolites, including phenolic compounds. This study aimed to determine the total phenolic content of these two endemic plants. Extraction was performed using Ultrasonic-Assisted Extraction (UAE), resulting in extract yields of 11.42% (11.42 g) for Dayak onion and 24.33% (24.33 g) for rose myrtle. Preliminary phytochemical screening using 1% FeCl₃ reagent indicated the presence of phenolic compounds, evidenced by a color change to bluish-green or dark green. The quantitative analysis was performed using UV–Vis spectrophotometry at a wavelength of 752 nm, applying the Folin–Ciocalteu method with gallic acid as the standard. The results showed that Dayak onion extract contained 1.410 mg GAE/g extract (0.141%), while rose myrtle extract contained 2.259 mg GAE/g extract (0.2259%) of total phenolic compounds. These findings highlight the phenolic potential of endemic medicinal plants from North Kalimantan and support their further exploration for pharmacological and nutraceutical applications